2013
DOI: 10.1186/0778-7367-71-13
|View full text |Cite
|
Sign up to set email alerts
|

Malnutrition: Prevalence and its associated factors in People living with HIV/AIDS, in Dilla University Referral Hospital

Abstract: BackgroundLiteratures on prevalence and factors associated with malnutrition among peoples living with HIV/AIDS are limited in Ethiopia and not well documented either. The proper implementation of nutritional support and its integration with the routine highly active antiretroviral therapy package demands a clear picture of the magnitude and associated factors of malnutrition. The objective of this study is, therefore, to assess the prevalence and factors associated with malnutrition among peoples living with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

39
85
12
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(139 citation statements)
references
References 13 publications
39
85
12
3
Order By: Relevance
“…In this study, those who had history of diarrhea in the last two weeks were 4.43 times at risk of having chronic energy deficiency than their counter parts. This findings consistent with the study conducted in Dilla(AOR = 3.40) [36] but not in a study done in Butajira and Humera [20,40].…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…In this study, those who had history of diarrhea in the last two weeks were 4.43 times at risk of having chronic energy deficiency than their counter parts. This findings consistent with the study conducted in Dilla(AOR = 3.40) [36] but not in a study done in Butajira and Humera [20,40].…”
Section: Discussionsupporting
confidence: 82%
“…Similarly, a study conducted in Nepal and Dilla revealed that Illiterate people were 2.3 and 3.5 times more likely to be chronic energy deficient as compared to people who can read and write respectively [34,36]. A meta-analysis done among women living with HIV in SSA also supports this finding [13].…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…It is also important to point out that the HIV has mechanisms that affect specifically the nutritional status of individuals by increasing the energy demand and interfering in the absorption and metabolism of the nutrients. (18) The consumption of illegal drugs, alcohol, and tobacco is seen by some authors as a risk factor for developing opportunistic infections in patients with AIDS. Oral candidiasis and hairy leukoplakia are some examples of these infections.…”
Section: Discussionmentioning
confidence: 99%